2002
DOI: 10.1590/s0101-74382002000300004
|View full text |Cite
|
Sign up to set email alerts
|

Cooperação entre redes neurais artificiais e técnicas 'clássicas' para previsão de demanda de uma série de vendas de cerveja na Austrália

Abstract: * Corresponding author / autor para quem as correspondências devem ser encaminhadas Recebido em 07/2002, aceito em 12/2002 após 1 revisão ResumoO principal objetivo deste trabalho é avaliar a complementação do uso de técnicas de previsão de vendas com Redes Neurais Artificiais. Como aplicação, foi analisada a demanda industrial no setor de cerveja da Austrália. A maioria dos modelos de previsão atuam de forma isolada, ou seja, tratando problemas por enfoques que se excluem. A sugestão deste trabalho é utilizar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 3 publications
0
5
0
7
Order By: Relevance
“…When employing a neural model, Nelson et al (1999) observed forecasts that are more accurate with seasonally adjusted data if compared to those collected without such pre-processing. Researchers as Calôba et al (2002) performed deseasonalization of data through trend removal, and then withdrawal cycles.…”
Section: Normalizationmentioning
confidence: 99%
“…When employing a neural model, Nelson et al (1999) observed forecasts that are more accurate with seasonally adjusted data if compared to those collected without such pre-processing. Researchers as Calôba et al (2002) performed deseasonalization of data through trend removal, and then withdrawal cycles.…”
Section: Normalizationmentioning
confidence: 99%
“…Many organizations use demand prevision to plan their goals and strategies. Calôba et al (2002) claim that companies exist to serve consumers with their products or services, thus forecast demand aims to assess the response of the end customer and plan measures to meet it in the most efficient manner. Tubino (2007), points out that the demand prevision can be assessed using quantitative and qualitative methods, and serves as a basis for strategic planning in production levels, sales and finance.…”
Section: Demand Previsionmentioning
confidence: 99%
“…Published works about forecast demand have analyzed various products, such as beer (Calôba, Calôba, and Saliby, 2002); fresh milk (Doganis, Alexandridis, Patrinos, and Sarimveis, 2006); other perishable products (Higuchi, 2006); food retail (Zotteri;Kalchschmidt, and Caniato, 2005); wireless subscribers (Venkatesan and Kumar, 2002); supermarket sales (Taylor, 2007), number of births (Souto, Baldeon, and Russo, 2006); plastic products (Pellegrini and Fogliatto, 2000); price forecast (Medeiros, Montevechi, Rezende, and Reis, 2006); and analysis of stock market indicators (Faria, Albuquerque, Alfonso, Albuquerque, and Cavalcante, 2008), among others.…”
Section: Formula Applicationmentioning
confidence: 99%